Implementation Of Character Education In State Elementary School - Yusnan, Muhammad (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
Education is one of the most important factors in building and shaping one's character. The purpose of this research is to find out what the implementation of character education in State Elementary School 2 Nganganaumala is and to describe how character education is implemented in this school. This research method uses descriptive qualitative which is intended to describe and describe existing phenomena, both natural and empowering respondents, who pay more attention to the characteristics, quality, and interrelationships between research activities. The findings of this study indicate that: 1) the character values ​​applied are religious, responsibility, honesty, and tolerance. 2) Through habituation, implementation and concept of character education in State Elementary School 2 Nganganaumala. 3). The teacher's character education strategies include always reminding students of good things, issuing warnings, setting examples or being role models, engaging in routine or habituation activities, and increasing student awareness. 4) Barriers to the implementation of character education in State Elementary School 2 Nganganaumala are the factors of teachers, parents, environment, and students